Spectroscopic diagnostic of electron density for four-level system by collisional excitation model. Issue 4 (21st April 2021) - Zhen, Zhiqiang; He, Jian
Abstract: For accurate electron density diagnostics of plasma, the spectral diagnostics for four-level system instead of three-level system by collision excitation model are investigated. Taking the first four levels of magnesium VIII ion as an example, the relationship of electron density with line ratio is discussed, for a large region of electron density. Results show that when the electron density varies from 10 11  cm −3 to 10 13  cm −3, the electron density decreases with increasing of line ratio; at a same line ratio, the electron density obtained from the four-level system is smaller than that from the three-level system; at low electron density limit, the line ratio is 2, while at high electron density limit, the line ratio is 0.0467, which are both in good agreement with the theoretical predicted value. This discussion is significant in spectral diagnostics of plasma.